A Readily Accessible Class of Chiral Cp Ligands and their Application in RuII‐Catalyzed Enantioselective Syntheses of Dihydrobenzoindoles. (6th April 2018) - Wang, Shou‐Guo; Park, Sung Hwan; Cramer, Nicolai
Abstract: Chiral cyclopentadienyl (Cp x ) ligands have a large application potential in enantioselective transition‐metal catalysis. However, the development of concise and practical routes to such ligands remains in its infancy. We present a convenient and efficient two‐step synthesis of a novel class of chiral Cp x ligands with tunable steric properties that can be readily used for complexation, giving Cp x Rh I, Cp x Ir I, and Cp x Ru II complexes. The potential of this ligand class is demonstrated with the latter in the enantioselective cyclization of azabenzonorbornadienes with alkynes, affording dihydrobenzoindoles in up to 98:2 e.r., significantly outperforming existing binaphthyl‐derived Cp x ligands.